Role stressors in Australian transport and logistics workers: Psychosocial implications. (November 2018) - Tucker, Michelle K.; Jimmieson, Nerina L.; Jamieson, Jane E.
Highlights: Psychosocial injury is an important issue for the transport and logistics sector. Role stressors had interactive as opposed to additive effects. Low role conflict and low role ambiguity insulated employees from high role overload. When role ambiguity and role conflict were high, strain and morale were compromised. Abstract: Psychosocial injury is an important issue for the transport and logistics sector. Indeed, these workers typically face multiple role stressors that compromise mental health and, in turn, have a deleterious effect on safety outcomes. The present study investigated the interactive effects of three roles stressors on employee strain (psychological strain and sleep disturbances) and employee morale (job dissatisfaction and turnover intentions) in 443 Australian road transport and logistics workers. Regression analyses using PROCESS revealed significant three-way interactions among role overload, role ambiguity, and role conflict. When both role ambiguity and role conflict were low, the negative consequences of role overload on employee outcomes were buffered. In other words, low role conflict and low role ambiguity helped insulate employees from the impact of role overload. Conversely, when both role ambiguity and role conflict were high, psychological strain, sleep disturbances, job dissatisfaction, and turnover intentions remained high, regardless of the level of role overload. Implications for theory and practice in the transport and logistics sector are discussed.